2018
DOI: 10.1016/j.msea.2017.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of testing mode on the fatigue behavior of <111> austenitic grain at the nanometric length scale for TRIP steels

Abstract: Metastable austenitic stainless steels, and in particular the TRansformation Induced Plasticity steels, rely on a phase transformation from a ductile austenite to a slightly harder martensite. These materials under fatigue testing conditions at the macrometric length scale can induce a softening or hardening effect as a function of the underlying deformation feature activated. Thus, given the interaction of single grains in polycrystalline materials, the collective response to macroscopic fatigue testing is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Las pruebas de nanoindentación realizadas bajo el modo de control de carga se pueden comparar con las pruebas de fatiga de bajo ciclo (lcf), donde la contribución de la deformación plástica es predominante en relación con la deformación elástica del total de la deformación. Por otro lado, cuando los experimentos se realizaron bajo el modo de control de desplazamiento, se asemejan a las pruebas de fatiga de alto ciclo (hcf), donde la deformación elástica es más significativa [6]. Para entender el comportamiento de una aleación Fe-20Mn-3Al-0.9C, clasificada como un acero twip (plasticidad inducida por maclas, por sus siglas en inglés) mediante estudio previo [11], la muestra fue sometida a cargas dinámicas de nanoindentación, considerando el control de carga y el control de desplazamiento, como se analizará a continuación.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…Las pruebas de nanoindentación realizadas bajo el modo de control de carga se pueden comparar con las pruebas de fatiga de bajo ciclo (lcf), donde la contribución de la deformación plástica es predominante en relación con la deformación elástica del total de la deformación. Por otro lado, cuando los experimentos se realizaron bajo el modo de control de desplazamiento, se asemejan a las pruebas de fatiga de alto ciclo (hcf), donde la deformación elástica es más significativa [6]. Para entender el comportamiento de una aleación Fe-20Mn-3Al-0.9C, clasificada como un acero twip (plasticidad inducida por maclas, por sus siglas en inglés) mediante estudio previo [11], la muestra fue sometida a cargas dinámicas de nanoindentación, considerando el control de carga y el control de desplazamiento, como se analizará a continuación.…”
Section: Resultados Y Discusiónunclassified
“…De esta manera, en los primeros ciclos de descarga, los granos de la austenita se recuperan levemente de la deformación plástica inducida en el proceso indentación, sin embargo, en la siguiente carga, el indentador penetra nuevamente la misma zona, aumenta la deformación plástica del ciclo anterior y por ende, de la profundidad, así, produce un ablandamiento del material. Este proceso de ablandamiento se puede deber a la nucleación y propagación de dislocaciones de alta densidad consecuencia del proceso cíclico [6]. En la figura 1c se muestra que los niveles de carga se mantienen durante los 100 ciclos, pero la profundad de indentación aumenta con el paso de los ciclos, esto genera un ablandamiento del material.…”
Section: Control De Cargaunclassified
See 1 more Smart Citation
“…The experiments were conducted using a nanoindenter, where the tested volume is comparable to the microstructure to the NG structure [21,23] and the experimental conditions are identical. Nanoindentation technique was beneficial for studying micro/nanoscale deformation behavior of austenitic stainless steels and transformation-induced plasticity (TRIP) steels [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dynamic deformation was examined by means of cyclic nanoindentation, concluding that metastable stainless steels present an inelastic nature of the unloading/reloading response which is mainly related to the ratcheting effect [14]. The influence of testing mode on the fatigue behavior was also studied, and the results showed that nanoindentation under loading control mode could be compared to conventional low-cycle fatigue tests, whereas the experiments performed under displacement control mode may be associated with high-cycle fatigue tests [15]. Additionally, the dependence of nanoindentation hardness on the crystallographic orientation of austenitic grains was analyzed [8].…”
Section: Introductionmentioning
confidence: 99%